On the influence of test speed and environment in the fatigue life of small diameter nitinol and stainless steel wire. (February 2022) - Weaver, J.D.; Sena, G.M.; Falk, W.M.; Sivan, S.
Highlights: The influence of speed and environment on low and high cycle fatigue was studied. Rotary bend fatigue experiments examined nitinol and stainless steel wires. Low cycle fatigue life in deionized water increased with faster test speed. Electropotential monitoring was presented as a way to characterize crack growth. Abstract: To better understand the complex interplay of speed and environment on metals commonly used in implants, rotary bend fatigue tests were conducted on stainless steel and nitinol wires. A range of alternating strains was tested to create ε-N curves at two speeds (physiologic and accelerated) and in three environments (deionized water at body temperature, phosphate buffered saline at body temperature, and laboratory air at ambient room temperature). Results indicate that speed and environment can affect the observed fatigue life in nuanced ways. An electropotential monitoring technique was demonstrated to characterize fatigue crack growth which may be useful in future investigations.